The Roma in Romanian History - Viorel Achim (Central European University Press, 1998)
One of the greatest challenges during the enlargement process of the European Union towards the east is how the issue of the Roma or Gypsies is tackled. This ethnic minority group represents a much higher share by numbers, too, in some regions going above 20% of the population. This enormous social and political problem cannot be solved without proper historical studies like this book, the most comprehensive history of Gypsies in Romania. It is based on academic research, synthesizing the ent...
English
Keywords: emancipation; racism; Romania; minority studies; gypsies$1 (Bmigrations; Romanies; sedentarisation; social situation; Moldavia; nomadism; assimilation; slavery; integration; Southeastern Europe; social organisation; deportation; gypsies